2017
DOI: 10.1021/acs.langmuir.7b01936
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Particle Formation in Silver/Epoxy Nanocomposites Obtained through a Visible-Light-Assisted in Situ Synthesis

Abstract: A detailed understanding of the processes taking place during the in situ synthesis of metal/polymer nanocomposites is crucial to manipulate the shape and size of nanoparticles (NPs) with a high level of control. In this paper, we report an in-depth time-resolved analysis of the particle formation process in silver/epoxy nanocomposites obtained through a visible-light-assisted in situ synthesis. The selected epoxy monomer was based on diglycidyl ether of bisphenol A, which undergoes relatively slow cationic ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“… 3 , 20 This is of great interest and was recently actively explored also in the case of non silicatic fillers. 21 , 22 When dealing with sol–gel chemistry, if the reaction rates are comparable, an interpenetrating network may also be obtained from the simultaneous reactions of the organic monomer and the sol–gel precursor. 20 In addition, the sol–gel route offers the formation of an inorganic phase starting from simple low-molecular-weight precursors, allowing a nanolevel molecular design of the final structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 20 This is of great interest and was recently actively explored also in the case of non silicatic fillers. 21 , 22 When dealing with sol–gel chemistry, if the reaction rates are comparable, an interpenetrating network may also be obtained from the simultaneous reactions of the organic monomer and the sol–gel precursor. 20 In addition, the sol–gel route offers the formation of an inorganic phase starting from simple low-molecular-weight precursors, allowing a nanolevel molecular design of the final structure.…”
Section: Introductionmentioning
confidence: 99%
“…Very often, unprecedented materials were produced whose properties are not simply a combination of the two components alone . A common way to develop these materials is the use of the sol–gel synthesis route. The mild synthesis conditions in the sol–gel process allow generating an inorganic phase in the presence of the monomer or the polymer through the so-called “ in situ ” process, in which both phases are formed successively in one procedure. , This is of great interest and was recently actively explored also in the case of non silicatic fillers. , When dealing with sol–gel chemistry, if the reaction rates are comparable, an interpenetrating network may also be obtained from the simultaneous reactions of the organic monomer and the sol–gel precursor . In addition, the sol–gel route offers the formation of an inorganic phase starting from simple low-molecular-weight precursors, allowing a nanolevel molecular design of the final structure.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, silver nanoparticles are easy to clump into agglomerates due to their ultrafine size, and silver salts are difficult to dissolve in hydrophobic dental resin monomers, which are challenges faced in AgNP applications [ 40 ]. In situ synthesis methods can avoid agglomeration formation during the procedure of mixing AgNPs into resin [ 41 ]. Ren et al showed that AgNPs were successfully synthesized in the resin matrix by reducing silver ions in situ through photoinitiation and proved to have good antibacterial effects [ 42 ].…”
Section: Current Antimicrobial Strategies Of Resin Compositesmentioning
confidence: 99%
“…Furthermore, by varying the solar flux, the authors were able to control the NP size distribution and, therefore, the final plasmonic response of the nanocomposite. Alternatively, metal/polymer nanocomposites can be obtained through a simultaneous reduction–polymerization approach. Yagci et al demonstrated that UV-generated free radicals can initiate the polymerization of an acrylic resin, and at the same time, they can reduce a Au­(III) precursor to Au(0) . In this way, gold particle formation and matrix polymerization occur simultaneously in a one-pot process.…”
Section: Introductionmentioning
confidence: 99%